Environmental Performance in the Era of Industry 4.0: The Role of Corporate Digital Responsibility, Green Capability, and Environmental Dynamism - Zainab, Bibi; Ghani, Bilqees (Journal of Development and Social Sciences, 2024)
The objective of this study is to investigate the relationships between corporate digital responsibility and the ability of businesses to accomplish environmental goals. In addition, we investigate how environmental dynamics improve environmental performance. Although corporate digital responsibility has been shown to improve operational and financial performance, there may be unanticipated environmental consequences. To address these concerns, this paper investigates how firms might build a portfolio of technologies to achieve their corporate digital responsibility (CDR) goals. It refers to the companies’ ability to execute digital corporate responsibility. Close ended questionnaire was used. A survey of 319 Pakistani manufacturing firms revealed a significant correlation between corporate digital responsibility and environmental performance. The data support the premise that green competence mediates the link between corporate digital responsibility and environmental performance. The results do not support the hypothesis that the usage of environmental dynamism moderates the association between corporate digital responsibility and environmental performance. We suggest employing a mixed-methods strategy that combines both in-depth qualitative research and advanced quantitative analyses. As a result, companies are unable to utilize the synergies between CDR and environmental dynamism to achieve higher levels of EP.